In-situ Noise Measurement and Analysis for the Motorcycle Muffler - Tan, Wei-Hong; Chuah, Hun-Guan; Cheng, Ee-Meng; Lim, Eng-Aik; Lok, Chip- Hao (International Journal of Integrated Engineering, 2020)
Noise from the vehicles is one of the noise pollution to the environment. The noises emitted by the vehicles have to obey the requirement of regulation of maximum sound pressure level permitted for respective vehicles. In this study, the aim is to reduce the noise emitted from the motorcycle muffler. The noise emitted from the motorcycle muffler is analyzed and measured using a sound level meter. The average sound pressure level of the motorcycle muffler is determined in certain conditions. The sound pressure level is obtained from original motorcycle muffler, when it is under constant speed (10 km/hr, 20 km/hr, 30 km/hr) and under acceleration (in the scope of 0 km/hr to 30 km/hr). The study is continued by using a modified motorcycle muffler which contains sound absorptive materials. The absorptive materials chosen are glass wool, cotton and Styrofoam and they are taking turn to be placed into the motorcycle muffler to reduce the sound pressure level. Then the experiment is repeated. It is found that Styrofoam does not perform significantly in absorbing sound or noise in this study. Glass wool demonstrates relatively better sound energy absorption compared with cotton. In general, soft and porous materials are considered good performance in sound absorption. Denser materials are better at soundproofing or sound blocking. Therefore, glass wool with relatively higher density among the investigated absorptive materials in this study has the greatest sound absorption performance.